TINJAUAN YURIDIS TERHADAP PERLINDUNGAN ANAK DALAM RUANG SIBER DI INDONESIA - Hertianto, Muhammad Rafifnafia (Jurnal Hukum & Pembangunan, 2021)
Indonesia high internet development and penetration rate make the child as user in a vulnerable position tocyberspace threat. Ironically Indonesia until this moment has no specific law or technical mechanism that can guarantee child security and fulfill child rights. In the current situation the number of criminal reports which utilize internet as its medium arehigh and keep on increasing over the year. This research aim to analyze the concept of child protection in cyberspace based on existing regulations on child protection. This research uses normative juridical methods and secondarydata which is then analyzedto state conclusion and recommendation. Based on the analysis which has been done thus it can be concluded that child protection in cyberspace concept that appropriate and applicable in Indonesia that is by multi stakeholder participation, which consisting of government,social society, parents, and private sector and use multi approach methods by adopting suggested approach by International Telecommunication Union which consisting of legal, technical, organizational, capacity building, and internationalcooperation measures.